2013
DOI: 10.1111/sdi.12046
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Surgical Preference and Practice in Hemodialysis Vascular Access Creation

Abstract: Understanding healthcare providers' preferences, values, and beliefs around AVF eligibility is important to explain variability in practice. We conducted a survey of international surgeons, using hypothetical patient scenarios, to assess resources used, variables, perceived barriers, and absolute contraindications to access creation. A total of 134 surgeons completed the survey. Venous duplex ultrasound mapping (VDUM) was offered to all patients by 90% of US, 68% Canadian, and 63% European respondents. VDUM al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 50 publications
1
28
1
Order By: Relevance
“…Additionally, Canadian patients and health care providers have attitudes that are markedly different from the rest of the world, and it would seem that Canada has a culture that is more permissive of catheters (22). In surveys, we have found that this attitude is pervasive among patients, and nephrologists as well as vascular access surgeons had marked variations in their practices regarding AV access referral patterns and creation, respectively (26,28,29). (1-3).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Canadian patients and health care providers have attitudes that are markedly different from the rest of the world, and it would seem that Canada has a culture that is more permissive of catheters (22). In surveys, we have found that this attitude is pervasive among patients, and nephrologists as well as vascular access surgeons had marked variations in their practices regarding AV access referral patterns and creation, respectively (26,28,29). (1-3).…”
Section: Discussionmentioning
confidence: 99%
“…There is no systematic evidence that preoperative US mapping will induce an increase in the proportion of fistulas ultimately used for dialysis or a reduction in catheter use. It appears that the results from vessel mapping only influenced the decision as to the type or location of the AV access in surgeons with less than 15 years of experience [101]. In patients with pre-operative vascular mapping, on multiple variable logistic regression, factors associated with failure to mature were female gender, age > 65 years and forearm location (up to 78% if the three criteria were met), and the extracted mapping hemodynamic measurements could not differentiate patients with mature or immature forearm fistulas [102].…”
Section: Prevention Of Early Complicationsmentioning
confidence: 99%
“…Surgeons in both programs share a common goal of creating fistulas as the initial access when possible (28); however, the clinical or radiologic evaluation of patient suitability for a fistula may vary by surgeon (29). Patient information is entered prospectively into a vascular access database that is managed by a multidisciplinary vascular access team that includes trained data-entry staff.…”
Section: Participants and Study Designmentioning
confidence: 99%